Perspective directions of research on the prevention of morbidity and traumatism of the members of vessel`s crew of the river transport fleet during the development of the Northern Sea Route - Shapovalov KA; Shapovalova PK (Annals of Marine Science - Peertechz Publications, 2018)
The new stage of development of the Northern Sea Route, the only highway connecting the subarctic and arctic regions of the Russian Federation, involves the development of a transport system, the complex of which includes all the rivers flowing into the Arctic Ocean. Despite the large number and vastness of the river basins in the Russian Federation, their importance for the effective operation of the country's economy, the problem of preventing traumatism of the members of vessel`s crew of the river transport fleet was reflected in research by a small number of practitioners, individual scientists and medical research teams. Improving the performance of the health care system; ensuring the availability and quality of medical care to the members of vessel`s crew of the river transport fleet, the formation of sustainable industrial motivation and conscious attitude to their health for this contingent of industrial workers, striving for a high health culture and a healthy lifestyle as the basis of a long-term and full-fledged life; The creation of a positive attitude towards the health care system at the river men is the stated goal of the organizational and methodological work of the medical service of the river fleet. To do this, it is necessary to specify the state guarantees for providing free medical care to the members of vessel`s crew of the river transport fleet, to create an effective model for managing the financial resources of these guarantees, and to improve the provision of outpatient medication to water workers as part of the compulsory health insurance system. This is not possible without improving the qualifications of medical workers and creating a system for motivating them to quality work, developing medical science and innovation, and informatization of water transport healthcare.